Molecular Docking and in vitro Enzyme Assay of Bioactive Compound Isolated from Rhus tripartite Collected from Hail Region of Saudi Arabia as Potential Anti-Diabetic Agent - Unnisa, Aziz; Kunduru, Rama Devi; Jandrajupalli, Suresh Babu; Elamine, Badria Awad; Banu, Humerah; Baratam, Anupama; Khan, Sharukh (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: In the present investigation, we have studied the inhibitory potential of a bioactive compound isolated from Rhus tripartite on Glucokinase (GK), Dipeptidyl Peptidase-IV (DPP-IV), alpha-glucosidase, and alpha-amylase enzymes. Materials and Methods: The plant leaves were subjected to Soxhlet extraction followed by qualitative phytochemical screening and the separation of active constituents by applying column chromatography. The obtained fraction was subjected to spectral analysis to identify the compound. Molecular docking followed by in vitro enzyme assays were used to study the inhibitory effect of the isolated compound. Results: The plant leaves were used for the extraction, and the identified compound was S-benzo[d]oxazol-2-yl 2-(piperazine-1-yl)ethanethioate, confirmed by spectral analysis. From in-silico ADMET analysis, the isolated compound displayed most drug-likeness features, and in molecular docking studies, it has developed many crucial hydrogen bonding and hydrophobic interactions with enzymes (PDB IDs: 1V4S, 2P8S, 3BAX, and 3WY2). An in vitro enzyme assay validated the virtual screening results of isolated compounds. Isolated compound at 250 μgm/ mL displayed 96.29±2.56, 89.23±2.1, 72.72±0.75, and 69.76±0.85% activity against GK, DPP-IV, alpha-amylase, and alpha-glucosidase enzymes, respectively. Conclusion: Our study concluded that DM could be treated using an isolated compound after further in-vivo and in-vitro studies.
Keywords: DPP-IV; in-vitro; Rhus tripartite; Isolation; Characterization